Waste to wealth in building materials development: a review of plastic waste in concrete - Anum, I.; Job, O. F. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Recently, there has been a growing interest in the use of post-consumer plastics in the production of concrete. Consequently, a large number of studies reporting the behaviour of concrete containing waste and recycled plastics have been published. These studies have great potential for improving the inherent weakness of concrete, reduction of pressure induced on the environment and creation of employment opportunities for economic development. This paper presents a review of journal publications on the effects of waste and recycled plastic materials on some fresh and hardened properties of concrete. The effects of waste plastic materials on slump, density, compressive strength, tensile/flexural strength and permeability are discussed. It was concluded that Post-consumer plastics can be successfully and effectively utilized to replace conventional concrete. This presents a strong potential for the production of sustainable concrete as well as meeting the goals of sustainable development requiring a waste to resource approach. The study suggests public education and awareness on the prospects of using waste plastic in concrete for economic empowerment among the population.